Fiscal reform and structural change in developing countries - Perry, Guillermo; Whalley, John; McMahon, Gary (Macmillan Press Ltd, 2000)
Fiscal Reform and Structural Change in Developing Countries analyzes the experience of countries involved in major tax reforms in the 1980s and first half of the 1990s by a combination of qualitative and quantitative country studies and over-arching thematic studies.